IFAS Community Development: Identifying Local Power Structures, The Decision-Making Approach - Mark A. Brennan (EDIS)
FCS9258, a 2-page fact sheet by M.A. Brennan, is part of a series of discussions on community development. This paper focuses on the decision-making approach to identifying community power structures. It discusses the assumptions, the procedures for application, the types of leaders identified, and the advantages and disadvantages of this approach. Includes references and suggested reading. Published by the UF Department of Family Youth and Community Sciences, July 2006.